Gastrointestinal Motility Disorders in Children - Prapun Aanpreung (Siriraj Medical Journal, 2020)
From 1991 to 2000, thirty patients with gastrointestinal motility disorders were diagnosed in Department of Pediatrics, Siriraj Hospital. They were divided into 3 groups ; in group 1, 15 patients had normal psychomotor development with chronic intestinal pseudo-obstruction (CIP) or intestinal dysmotility; in group 2, 9 patients had psychomotor retardation with CIP or intestinal dysmotility and in group 3, 6 patients had gastroparesis. Three cases in group 1 had underlying causes including megacystis-microcolon-intestinal-hypoperistalsis syndrome (MMIHS), SLE, and Strongyloid infestation. MMIHS was diagnosed during pregnancy. This patient did not respond to any medications and died at 5 months. Nine cases in group 2 and 1 case in group 1 were diagnosed as CIP due to their persistent symptoms of obstruction and radiologically demonstrated dilated intestine with air /fluid levels. The main presenting symptoms were abdominal distention (27 cases), constipation (14 cases), abdominal pain (13 cases), vomiting (9 cases), diarrhea (9 cases), and refusal of feeds (3 cases). X-ray studies were the most useful investigation to diagnose the disorders. All patients received cisapride as a prokinetic drug in order to improve the motility of the GI tract. A good response was obtained in14 cases, a fair response in 15 cases and a poor response in 1 case. GI motility disorder is not uncommon in Thai children. The severity of the motility disorder varied from mild to severe. The majority of cases had a good prognosis except in the cases with psychomotor retardation.